MEDIA PEMBELAJARAN SISTEM PERIODIK UNSUR DENGAN KONSEP JEMBATAN KELEDAI MENGGUNAKAN TEKNOLOGI AUGMENTED REALITY BERBASIS ANDROID - Anggi Wulandari; M Fakhriza (JISTech (Journal of Islamic Science and Technology), 2021)
Augmented Reality is a technology that unites the real world view with the virtual world in real time. Augmented Reality has been widely used in various fields, one of which is education. Augmented Reality can be used by students to make it easier to learn the periodic system. The mnemonic concept is a concept that is used to help students remember vocabulary information more quickly and easily. In this study, a learning media application for the periodic system of elements was developed using the mnemonic concept that utilizes Augmented Reality technology that can help students understand and remember material related to the periodic system of chemical elements. This application is made with Blender 3D software to create 3D atomic structure objects and their uses, Vuforia SDK and Unity 3D for building applications and marker detection. The final result of making this learning media application is Augmented Reality which can display 3D objects from the atomic structure and uses of these elements as well as mnemonic concepts from groups IA to VIIIA. This application uses a Markerless Based Tracking technique. From the tests that have been carried out on users, it is concluded that the applications built are suitable for use